Bioluminescence in the high Arctic during the polar night - Berge, Jørgen; Båtnes, Anna Solvang; Johnsen, Geir; Blackwell, Susan; Moline, Mark A. (Marine Biology, 2012)
This study examines the composition and activity of the planktonic community during the polar night in the high Arctic Kongsfjord, Svalbard. Our results are the first published evidence of bioluminescence among zooplankton during the Arctic polar night. The observations were collected by a bathyphotometer detecting bioluminescence, integrated into an autonomous underwater vehicle, to determine the concentration and intensity of bioluminescent flashes as a function of time of day and depth. To further understand community dynamics and composition, plankton nets were used to collect organisms passing through the bathyphotometer along with traditional vertical net tows. Additionally, using a moored bathyphotometer closed to the sampling site, the bioluminescence potential itself was shown not to have a diurnal or circadian rhythm. Rather, our results provide evidence for a diel vertical migration of bioluminescent zooplankton that does not correspond to any externally detectable changes in illumination.